Environmental Geochemistry and Health Report to the Royal Society$1 (Bs British National Committee for Problems of the Environment /s - Bowie, S.H.; Thornton, I.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 1985)
One of the main outcomes of the eleven meetings of the Working Party was the recognition of the importance of interdisciplinary studies linking regional geochemistry with plant, animal and human health. The effects of major element deficiencies or excesses on plant health are well known; this is not the case for trace elements. In fact, rapid and reliable analytical methods for determining trace element abundances have only recently become available, and it is to be expected that important new information on trace element levels will be forthcoming. This, however, is only part of the problem because other factors such as element speciation, uptake and transmission may be more significant than total concentration. The pathways of elements from crops to animals are relatively well defined, but the aetiology of diseases attributable to elemental inadequacies or excesses is generally quite complex. Nevertheless, there is good evidence for diseases in livestock in the British Isles induced by deficiencies of Cu, Se and Co and Mo excess. On a world scale there is also convincing data on the effect of Na, P and I deficiencies and F excess on animal health. What is generally lacking, however, is adequate interaction between geochemists and biochemists, veterinary scientists and other concerned with animal health. Interpretation of geochemical data is complex as are connections between elemental abundances and the health of animals.
1. Introduction -- 1.1. Origins and Remit -- 1.2. Actions Taken -- 1.3. Royal Society Working Party on Environmental Geochemistry and Health -- 2. Principles Of Environmental Geochemistry -- 2.1. Summary -- 2.2. Introduction -- 2.3. The Distribution of Elements in Rocks and some Geochemical Associations -- 2.4. Redistribution of Chemical Elements by Weathering -- 2.5. Chemical Elements in the Surface Environment and Factors Influencing Redistribution -- 2.6. Uranium and Daughters -- 2.7. Regional Geochemical Maps -- 2.8. Regional Geochemistry of Britain -- 2.9. Trace Elements in Soils -- 2.10. Metal Pollution -- 2.11. References -- 3. Plant-Soil Processes -- 3.1. Summary -- 3.2. Introduction -- 3.3. Major Elements N, P, K, Ca, and Mg -- 3.4. Other Elements -- 3.5. The Availability of Elements: Plant Factors -- 3.6. The Availability of Elements in the Soil: Soil Factors -- 3.7. The Root-Soil System -- 3.8. Practical Crop Problems in Britain -- 3.9. The Availability and Need for Soil Information Relating to Geochemistry -- 3.10. References -- 4. Geochemistry And Animal Health -- 4.1. Summary -- 4.2. Introduction -- 4.3. Inorganic Element Deficiency Diseases -- 4.4. Inorganic Element Toxicity -- 4.5. Dietary Requirements -- 4.6. Factors Modifying the Response of Animals to their Geochemical Environment -- 4.7. Prediction of the Risks of Deficiency or Toxicity from Geochemical Survey Data -- 4.8. The Influence of Geochemical Anomalies upon Animal Health: An Appraisal of Field Evidence -- 4.9. Conclusions -- 4.10. References -- 4.11. Appendix: Relations between the Distribution of High-Mo Geochemical Anomalies and of Cu Deficiency in Cattle in Caithness, N.E. Sutherland -- 5. Geochemistry And Human Health -- 5.1. Summary -- 5.2. Introduction -- 5.3. Iodine and Fluorine -- 5.4. Cardiovascular Disease -- 5.5. Calcium, Magnesium, and Sodium -- 5.6. Cancers and Geochemistry -- 5.7. Multiple Sclerosis and Geochemistry -- 5.8. Anomalous Geochemical Areas -- 5.9. Trace Elements and Health -- 5.10. Blood Levels of Trace Elements -- 5.11. References -- 6. Conclusions -- 7. Recommendations.
Keywords: Environmental chemistry; Public health; Environmental Chemistry; Public Health